On the Relationship Between Asset Exemptions and Outstanding Tax Repayments in Chapter 7 Bankruptcy - Hackney, Donald D.; Brajcich, Andrew; Dugenske, Emma; Friesner, Daniel L. (Journal of Accounting and Finance, 2024)
Under a Chapter 7 bankruptcy filing, assets are liquidated and used to repay debts, in order of a Court-established priority. If not repaid through the liquidation process, some of these debts (especially certain types of unpaid taxes) survive the bankruptcy proceedings and must still be repaid. The U.S. Bankruptcy Code allows individuals filing under Chapter 7 to exempt certain assets from the liquidation process. More generous exemptions lead to a lower value of assets liquidated and used to repay creditors. This leads to an interesting decision problem. Do filers with exempt assets and tax debts choose to retain their exempt assets and allow the tax obligations to survive the bankruptcy process? Or do they use the liquidation process to reduce outstanding tax obligations? This manuscript empirically explores this issue. We find no statistically significant evidence suggesting that households with greater exempt assets accumulate or repay a greater proportion of tax debts. However, filers who own businesses are more likely to accumulate and repay tax debts through bankruptcy.